PERAN KAKAK ASUH BALI SEBAGAI GERAKAN SOSIAL BERBASIS PENDIDIKAN DI BALI - Krisnayadi, Made Chandra; Kebayantini, Ni Luh Nyoman; Sastri Mahadewi, Ni Made Angita (JURNAL ILMIAH SOSIOLOGI (SOROT), 2018)
ABSTRACT This research focuses on one of the social movement based on education in Bali named Kakak Asuh Bali. The role of Kakak Asuh Bali isreducing the problem of dropping out by providing pocket money for students who are vulnerable to drop out and live in remote areas. In reducing the dropout rate issues, KakakAsuh Bali has attempted several activities such as conducting fostered sibling survey,visiting fostered sibling's house and school andproviding social service to fosteredsibling's school. In conducting these activities, there were some (internal and external) challenges experienced by KakakAsuh Bali. The positive impact of the presence of KakakAsuh Balihas been perceived by fostered siblings, families ,the schools, fostered siblings and volunteers. The applied theory in this research is the rational choice theory from James Samuel Coleman. Keywords: Education, KakakAsuh Bali, Rational Choice, and Social Movement